Association of electrospinning with electrospraying: a strategy to produce 3D scaffolds with incorporated stem cells for use in tissue engineering - Braghirolli DI (Dove Medical Press, 2015)
Daikelly Iglesias Braghirolli,1,2 Fernanda Zamboni,1 Gerson AX Acasigua,1,3 Patricia Pranke1,2,4 1Hematology and Stem Cells Laboratory, Faculty of Pharmacy, 2Department of Materials Science, 3School of Dentistry, Universidade Federal do Rio Grande do Sul, Porto Alegre, Rio Grande do Sul, Brazil; 4Instituto de Pesquisas com Células-Tronco, Porto Alegre, Rio Grande do Sul, Brazil Abstract: In tissue engineering, a uniform cell occupation of scaffolds is crucial to ensure the success of tissue regeneration. However, this point remains an unsolved problem in 3D scaffolds. In this study, a direct method to integrate cells into fiber scaffolds was investigated by combining the methods of electrospinning of fibers and bioelectrospraying of cells. With the associating of these methods, the cells were incorporated into the 3D scaffolds while the fibers were being produced. The scaffolds containing cells (SCCs) were produced using 20% poly(lactide-co-glycolide) solution for electrospinning and mesenchymal stem cells from deciduous teeth as a suspension for bioelectrospraying. After their production, the SCCs were cultivated for 15 days at 37°C with an atmosphere of 5% CO2. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test demonstrated that the cells remained viable and were able to grow between the fibers. Scanning electron microscopy showed the presence of a high number of cells in the structure of the scaffolds and confocal images demonstrated that the cells were able to adapt and spread between the fibers. Histological analysis of the SCCs after 1 day of cultivation showed that the cells were uniformly distributed throughout the thickness of the scaffolds. Some physicochemical properties of the scaffolds were also investigated. SCCs exhibited good mechanical properties, compatible with their handling and further implantation. The results obtained in the present study suggest that the association of electrospinning and bioelectrospraying provides an interesting tool for forming 3D cell-integrated scaffolds, making it a viable alternative for use in tissue engineering. Keywords: bioelectrospraying, cell speed, mesenchymal stem cells, tissue engineering, 3D scaffolds